Kemampuan Komunikasi Matematis Siswa antara Model Pembelajaran Course Review Horay dan STAD - Riyanti, Rindu; Mardiani, Dian (Department of Mathematics Education Program IPI Garut, 2021)
Kemampuan komunikasi matematis siswa yang masih rendah menjadi permasalahan dalam penelitian ini. Tujuan dari penelitian ini untuk mengetahui perbedaan peningkatan kemampuan komunikasi matematis antara siswa yang mendapatkan model pembelajaran Course Review Horay dengan siswa yang mendapatkan model pembelajaran Student Teams Achievement Divisio. Metode penelitian yaitu kuasi eksperimen. Populasi dalam penelitian ini adalah siswa salah satu SMP Negeri di Garut dengan sampel siswa kelas VII C dan VII D, sebanyak 50 siswa. Analisis data dilakukan dengan uji normalitas, uji honogenitas, dan uji t, Hasil penelitian menunjukkan bahwa terdapat perbedaan peningkatan kemampuan komunikasi matematis antara siswa yang mendapatkan model pembelajaran Cause Review Horay dengan siswa yang mendapatkan model pembelajaran Student Teams Achivment Division. Kualitas peningkatan Kelas Cause Review Horay dan kelas Student Teams Achivment Division sama-sama menunjukan kriteria sedang, kelas Cause Review Horay menunjukan sikap yang baik dan kelas Student Teams Achivment Division menujukan sikap cukup. Students' low mathematical communication skills are a problem in this study. The purpose of this study was to determine the increase in mathematical communication skills between students who received the Course Review Horay learning model and students who received the Student Teams Achievement Division learning model. The research method is quasi-experimental. The population in this study were students of one of the state junior high schools in Garut with a sample of 50 students in class VII C and VII D. Data analysis was carried out by normality test, homogeneity test, and t-test. The results showed that there was an increase in mathematical communication skills between students who received the Cause Review Horay learning model and students who received the Student Teams Achievement Division learning model. The quality of improvement in the Class Cause Horay Review and the Student Teams Achievement Division class both show moderate criteria, the Horay Review Cause class shows a good attitude, and the Student Teams Achievement Division class shows a sufficient attitude.